PEMANFAATAN MODAL SOSIAL APPI DALAM PEMILIHAN KEPALA DAERAH DI KOTA MAKASSAR - Doe, Hidayat; Muhammad, Muhammad; Sukri, Sukri; Ariana, Ariana (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2020)
This article examines the comparison of the use of social capital owned by Appi in the election of candidates for mayor election of Makassar in the 2018 and 2020. The capitalwhich is identified in this study is Appi's network as part of the big family of the Bosowa Corporation and the Kalla Group, as well as a businessman who has an extensive business network. In analyzing the capital, the research use a qualitative approach with a descriptive method, which describes and compares how Appi as a candidate uses his social capital to gain voters in two different elections. This study was conducted by collecting data through electronic media, scientific documents, and purposive interviews. The results showed that there were differences in the use of social capital. Appi is able to maximize the use of network capital in the 2020 elections compared to the 2018 Makassar elections. The use of social capital was carried out by placing his network capital as the main basis for his winning team. The capital has an impact on team solidarity and it proves the effectiveness of network capital of Appi as an entrepreneur and also a relative of the Bosowa and Kalla Group extended families.